Efficacy of aqueous plant extracts against two spotted spider mite, Teteranychus urticae - Gajalakshmi, M; Jeyarani, S; Ramaraju, K (Indian Journal of Plant Protection, 2020)
Aqueous leaf extracts of Lantana camara, Vitex negundo, Gynandropsis gynandra, Cleome viscosa, Coleus aromaticus, fruit pulp of Sapindus marginatus, seeds of Annona squamosa, seed kernel of Pongamia pinnata, Azadirachta indica and rhizome of Acorus calamus were tested for their acaricidal and ovicidal activity under laboratory condition against two spotted spider mite, Tetranychus urticae at different concentration viz., 2.5, 5.0 and 10.0 per cent. The results showed that among ten different aqueous extract of botanicals, S. marginatus (10%) was found to have highest acaricidal and ovicidal activity against T. urticae with 99.17 and 98.67 per cent mortality, respectively, at 72 h after treatment. The standard check neem seed kernel extract NSKE (5%) was found to be on par with S. marginatus by recording higher acaricidal and ovicidal action of 96.67 and 90.00 per cent, respectively.